2016
DOI: 10.4149/av_2016_04_361
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of enteric viruses in enteritis-affected commercial broiler chickens in India

Abstract: Summary. -A study was conducted to detect and characterize the enteric viruses (chicken astrovirus, avian nephritis virus and avian orthoreovirus) present in flocks of commercial broiler chickens suffering from enteritis in Haryana, India. The intestinal contents were collected from 65 enteritis-affected flocks (cases) and tested by reverse transcription PCR (RT-PCR). Of these 65 cases, 35 (53.80%) were positive for a single virus and 26 (40.00%) for two viruses. The remaining four samples were negative for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…ORF1a encodes non‐structural proteins, ORF1b encodes RNA‐dependent RNA polymerase, and ORF2 encodes nucleocapsid proteins. Avastrovirus (AAstV) isolated from avian species (Bulbule et al, ; Fu et al, ; Kaithal, Jindal, Kumar, & Mor, ; Mándoki, Dobos‐Kovács, Bakonyi, & Rusvai, ; Ter Veen, de Bruijn, Dijkman, & de Wit, ) is one of the leading causes of diseases in birds such as nephritis in chickens, hepatitis and stunting in ducks and gout in goslings (Bidin, Lojkic, Tisljar, Bidin, & Majnaric, ; Liu et al, ; Jin et al, ; Liu, Jiang, Dong, Wang, & Zhang, ; Yang, Tian, Tang, & Diao, ; Zhang, Cao, et al, ; Zhang, Wang, Liu, Yang, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…ORF1a encodes non‐structural proteins, ORF1b encodes RNA‐dependent RNA polymerase, and ORF2 encodes nucleocapsid proteins. Avastrovirus (AAstV) isolated from avian species (Bulbule et al, ; Fu et al, ; Kaithal, Jindal, Kumar, & Mor, ; Mándoki, Dobos‐Kovács, Bakonyi, & Rusvai, ; Ter Veen, de Bruijn, Dijkman, & de Wit, ) is one of the leading causes of diseases in birds such as nephritis in chickens, hepatitis and stunting in ducks and gout in goslings (Bidin, Lojkic, Tisljar, Bidin, & Majnaric, ; Liu et al, ; Jin et al, ; Liu, Jiang, Dong, Wang, & Zhang, ; Yang, Tian, Tang, & Diao, ; Zhang, Cao, et al, ; Zhang, Wang, Liu, Yang, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…All CAstV and ANV of this study were clustered in a group of ORF1b polymerase gene phylogeny. Kaithal et al ( 46 ) analyzed the ORF1b genes of CAstV and ANV and revealed that Indian isolates of CAstV and ANV were aligned with circulating and Brazilian sequences of the respective viruses. It could be assumed that transboundary transmission of both viruses through neighboring borders may occur.…”
Section: Discussionmentioning
confidence: 99%
“…Astroviruses have been detected from poultry flocks and other domestic birds from various parts of the world [8,10,15,19]. In a previous study conducted in our laboratory, we detected the presence of CAstV and ANV in enteritis-affected broiler chicken flocks by virus specific reverse-transcriptionpolymerase chain reaction (RT-PCR) [11].…”
Section: Introductionmentioning
confidence: 97%
“…The isolation and characterization of CAstV has been reported from broilers exhibiting RSS and dead-in-shell chicks having hatchability problems [1,29]. Few recent reports also suggest CAstVs infection in poultry in India [3,11,23].…”
Section: Introductionmentioning
confidence: 99%